A Classroom for All: Innovative UDL-Based Instructional Models and Media for Students with Disabilities - Septiana, Fajar Indra; Mastiani, Emay; Suwandari, Lilis; Astuti, Eka Yuli; Pertiwi, Dwi Endah; Qohar, Hendri Abdul; Rachmah, Siti; Almarogi, Ahmad Mugni (CV. Rayyan Dwi Bharata, 2025)
This study aims to develop an inclusive learning model and media based on Universal Design for Learning (UDL) for blind and deaf-mute students in the Special Education Study Program, Faculty of Teacher Training and Education, Universitas Islam Nusantara. The study uses a qualitative descriptive approach and follows the ADDIE development model. Data were collected through needs assessment, interviews, and observation. The results show that blind students require auditory-based media compatible with assistive technologies, while deaf-mute students require media emphasizing visuals and text. The developed products include accessible digital modules and captioned videos usable by all students. The study concludes that a UDL-based learning design effectively accommodates the diverse needs of students in an equitable and inclusive manner.